2021
DOI: 10.1166/jon.2021.1795
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Rotating Flow of an Oldroyd-B Nanofluid with Relaxation-Retardation Viscous Dissipation

Abstract: The principal aim of this study is to explore the impact of relaxation-retardation viscous dissipation, nonlinear convection, variable chemical reaction, and nonlinear thermal radiation on the three-dimensional rotating flow of an Oldroyd-B nanofluid over an exponentially extended surface. The Buongiorno model that takes into account the Brownian movement and thermophoresis responsible for nanoparticle motion. Exponentially varying temperature and concentration associated with convective heat transfer coeffic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The effect of entropy generation and irreversibility ratio on the 3D flow of OBF is analyzed by Mburu et al [3] in the presence of retardation-relaxation viscous dissipation. The effect of relaxation-retardation viscous dissipation on the NF flow of 3D rotating OBF is illustrated by Nayak et al [4]. The theoretical treatment of the radiative stream of OBF was examined by Khan et al [5] with microorganisms past an exponentially stretching sheet.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of entropy generation and irreversibility ratio on the 3D flow of OBF is analyzed by Mburu et al [3] in the presence of retardation-relaxation viscous dissipation. The effect of relaxation-retardation viscous dissipation on the NF flow of 3D rotating OBF is illustrated by Nayak et al [4]. The theoretical treatment of the radiative stream of OBF was examined by Khan et al [5] with microorganisms past an exponentially stretching sheet.…”
Section: Introductionmentioning
confidence: 99%
“…Turkyilmazoglu [2] developed a slip nano uid model for the annuli ow by utilizing the dual nano uid and single relations of the nano uid model. Nayak et al [3] exploited the viscous dissipation consequences for illustrating the nano uids ow with Oldroyd-B base material via bidirectional space. Basir et al [4] performed the novel aspect of slip ow of nano uid with sensitivity insurance and bioconvection phenomenon.…”
Section: Introductionmentioning
confidence: 99%
“…Sami et al (2019) investigated the Prandtl method in the presence of microorganisms enclosed by an accelerating surface for Oldroyd B nanofluid. The 3D rotating flow of an Oldroyd B nanofluid with relaxation-retardation viscous dissipation was examined by Nayak et al (2021). It is found that modified Eckert number ameliorates the temperature of Oldroyd B Nanofluid.…”
mentioning
confidence: 99%